2017
DOI: 10.3892/ol.2017.7496
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between TAP detection and common digestive tract precancerous lesions

Abstract: The aim of the present study was to investigate the clinical significance of abnormal sugar-chain glycoprotein tumor abnormal protein (TAP) in the screening of common digestive tract pre-cancer colon adenocarcinoma lesions. A total of 50 colitis patients, 50 colon polyp patients and 50 colon adenocarcinoma patients admitted to our hospital from March, 2012 to May, 2014 were included. Fresh blood from patient's fingertips was collected and condensation staining was used to detect TAP expression. Positive expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The transporter associated with antigen processing (TAP) is necessary for T-cell recognition [18]. Recent studies have demonstrated that TAP plays a critical role in cell differentiation, proliferation, the development and progression of cancer [19][20][21]. In addition, TAP detection has been recognized as a new independent indicator for the course of chemotherapy and clinical monitoring of several type of cancers [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The transporter associated with antigen processing (TAP) is necessary for T-cell recognition [18]. Recent studies have demonstrated that TAP plays a critical role in cell differentiation, proliferation, the development and progression of cancer [19][20][21]. In addition, TAP detection has been recognized as a new independent indicator for the course of chemotherapy and clinical monitoring of several type of cancers [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have collected evidence on the critical role that TAP plays in the development and progression of cancer, as well as the regulation of cell proliferation, apoptosis, differentiation, and development. [7][8][9] In gastric cancer patients, the upregulation of TAP was significant compared to healthy volunteers. Also, progression-free survival (PFS) is evident among patients with high TAP levels.…”
Section: Discussionmentioning
confidence: 94%
“…Studies performed recently have proven that TAP remarkably affects cancer development and progression and regulates cell growth in terms of proliferation and apoptosis ( 7 9 ). Gastric carcinoma patients presented an obvious TAP upregulation relative to healthy participants.…”
Section: Discussionmentioning
confidence: 99%